An optimised multicast data transmission scheme in IEEE 802.16j wireless relay networks. (2018) - Wang, Hanwu; Pan, Lian; Zou, Huicong
Relay enabled wireless networks play a significant role in data transmission, as it not only extends the base station (BS) coverage range but also improves the transmission efficiency of those mobile station (MS) with poor channel conditions. Multicast transmission is an efficient transmission mode and quite suitable for the relay-based networks. However, how to perform the desired multicast transmission in wireless relay network has not been specified. To realise the effective multicast-based data delivery over the whole relay network, we propose an optimised transmission scheme by formulating an objective problem to achieve the desired performance goals. Specifically, an efficient multicast data transmission mechanism with respect to two schedule hops is proposed in detail to implement the optimisation process. Moreover, we also incorporate the spatial reuse into the transmission mechanism to improve the scheduling efficiency. The simulation results verify the efficacy and efficiency of the proposed transmission scheme.